2017
DOI: 10.1038/ismej.2017.129
|View full text |Cite
|
Sign up to set email alerts
|

Chemical dispersants enhance the activity of oil- and gas condensate-degrading marine bacteria

Abstract: Application of chemical dispersants to oil spills in the marine environment is a common practice to disperse oil into the water column and stimulate oil biodegradation by increasing its bioavailability to indigenous bacteria capable of naturally metabolizing hydrocarbons. In the context of a spill event, the biodegradation of crude oil and gas condensate off eastern Canada is an essential component of a response strategy. In laboratory experiments, we simulated conditions similar to an oil spill with and witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 92 publications
3
89
0
Order By: Relevance
“…However, all these studies, including this one, present some level of variation between successional patterns over time which reinforce the hypothesis that early and late microbial community assemblages are influenced by both deterministic and stochastic processes (Dini‐Andreote et al, ). However, when putting these taxonomic profiles in context with their corresponding oil degradation rates (Tremblay et al, ) Schreiber et al ., ), it appears that regardless of which oil degrading microbes are present, oil is being degraded.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, all these studies, including this one, present some level of variation between successional patterns over time which reinforce the hypothesis that early and late microbial community assemblages are influenced by both deterministic and stochastic processes (Dini‐Andreote et al, ). However, when putting these taxonomic profiles in context with their corresponding oil degradation rates (Tremblay et al, ) Schreiber et al ., ), it appears that regardless of which oil degrading microbes are present, oil is being degraded.…”
Section: Resultsmentioning
confidence: 99%
“…Usage of dispersant in oil spills remains controversial (Kleindienst et al, ). Some recent studies suggest that dispersants enhance oil degradation rates (Tremblay et al, ), whereas others found a negative impact (Kleindienst et al, ) or no impact (Brakstad et al, ). We previously reported that adding dispersant to oil slightly favoured n ‐alkane degradation in east coast microcosms (Tremblay et al, ) and did not have a significant impact in west coast microcosms (Schrieber et al , submitted).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations